Determinants of adoption of climate-smart agriculture technologies in rice production in Vietnam - Duyen, Tran Nhat Lam; Rañola, Roberto F.; Sander, Björn Ole; Wassmann, Reiner; Nguyen, Dinh Tien; Nong, Nguyen Khanh Ngoc (Emerald Publishing Limited, 2019)
Purpose In recent years, climate-smart agriculture (CSA) was introduced to Vietnam to enhance farmers’ resilience and adaptation to climate change. Among the climate-smart agricultural technologies (CSATs) introduced were water-saving techniques and improved stress tolerant varieties. This study aims to examine the determinants of farmers’ adoption of these technologies and the effects of their adoption on net rice income (NRI) in three provinces as follows: Thai Binh (North), Ha Tinh (Central) and Bac Lieu (South).